Is spinal block safe for cesarean delivery? – a case report of a patient with uncorrected type 1 Chiari malformation - Dahlem, Caroline Sobral; Pereira, Ana Isabel; Gomes, Tiago Vaz (Journal of the Portuguese Society of Anesthesiology, 2017)
Type 1 Chiari malformation is a downward displacement of the cerebellar tonsils with hindbrain overcrowding. The clinical picture is highly variable and their obstetric and anesthetic management is not consensual. We report the case of a patient with uncorrected type 1 Chiari malformation presenting for elective cesarean delivery in whom a spinal block was performed. Anesthesia and surgery were uneventful. Mother’s sole complaint was neck stiffness which was solved after 3 days. Literature is scarce reporting only 2 previous uncorrected type 1 Chiari malformation patients being submitted to spinal anesthesia for cesarean delivery. The safety of spinal anesthesia for this scenario is discussed.